THE CORPORATE GOVERNANCE ROLE OF LIFE INSURANCE COMPANIES AS INSTITUTIONAL INVESTORS - Abdalyan, Ani M. (Assurances, 1997)
The purpose of this article is to analyze goals of corporate governance and specifically relationships between shareholders, directors and management. The author discusses appropriate roles of institutional investors in the corporate governance process. She also discusses the behaviour of life insurance companies in the United States as institutional investors and compares it with the British experience. Finally, she analyzes the degree of activity in Canada by life insurance companies in corporate governance. ln this regard, some anecdotal evidence from a survey of life insurance companies is set out.